2022
DOI: 10.1002/aepp.13305
|View full text |Cite
|
Sign up to set email alerts
|

The effect of information nudges on online purchases of meat alternatives

Abstract: We investigated the effect of health and environmental information messages on purchases of meat and plant‐based alternatives in a non‐hypothetical online supermarket experiment. When controlling for observables, we find the health information nudge to be effective at motivating meat eaters to purchase plant‐based meat alternatives. This effect is absent when providing environmental information or its combination with health information. We also find that meat eaters implicitly perceive meat to be healthier bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Interestingly, after reading messaging about the benefits of PBFs in this study, participants’ likeliness to try PBFs and add PBFs into their regular diet increased. This result has also been found in other studies looking at PBMAs (Fiorentini et al., 2020; Gómez‐Luciano et al., 2019; Segovia et al., 2023). One study found that if participants believed that PBMAs were healthy, safe, and nutritious, their willingness to purchase increased by 68.7% (Gómez‐Luciano et al., 2019).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, after reading messaging about the benefits of PBFs in this study, participants’ likeliness to try PBFs and add PBFs into their regular diet increased. This result has also been found in other studies looking at PBMAs (Fiorentini et al., 2020; Gómez‐Luciano et al., 2019; Segovia et al., 2023). One study found that if participants believed that PBMAs were healthy, safe, and nutritious, their willingness to purchase increased by 68.7% (Gómez‐Luciano et al., 2019).…”
Section: Resultssupporting
confidence: 86%
“…One study found that if participants believed that PBMAs were healthy, safe, and nutritious, their willingness to purchase increased by 68.7% (Gómez-Luciano et al, 2019). Another study found that providing health messaging on PBMAs increased omnivores' willingness to purchase meat alternatives, although the same effect was not present with environmental messaging (Segovia et al, 2023). This result indicates that health messaging plays a role in consumer acceptance and choice; however, successful replication of complex sensory characteristics in PBFs still appears to be the main driving force for consumers liking and willingness to try PBFs alternatives.…”
Section: Texturementioning
confidence: 99%
“…Reviewing the literature on consumer motivations, Szejda and Perry (2020) suggest that producers of plant-based alternatives should emphasize the health benefits of plant-based products rather than their ethical attributes. This advice is echoed by Segovia et al (2022), who find that experimental subjects in the US are more likely to purchase meat alternatives when they receive information about the health benefits of reduced meat consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many plant‐based producers emphasize the benefits of their products for animal welfare and the environment. However, recent research has suggested that consumers may be more responsive to marketing that highlights the nutritional benefits of plant‐based products rather than ethical concerns (Segovia et al, 2022; Szejda & Perry, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation